Morus rubra, Red Mulberry - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS)
FOR 264, a 3-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this native deciduous tree found in the moist soils of mesic hardwood forests, floodplains, and other moist sites from south Florida, west to Texas, north to Minnesota, and the extreme southern portion of Ontario, Canada, and east to the Mid-Atlantic states – scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.